AN EMPIRICAL TEST OF A 14-DAY MONEY FLOW INDEX AND RELATIVE STRENGTH INDEX HYBRID’S PREDICTIVE ABILITIES ON HELSINKI, OSLO AND STOCKHOLM STOCK EXCHANGES - Tolonen, Tuomo (My University, 2011)
Technical analysis has been used in stock market forecasts for more than a century and it is one of the basic applications of the modern day finance. However these methods have for decades raised conflicting opinions in the science community, leaving the field a subject of disdain by academics. The purpose of this thesis is to test whether a hybrid of money flow index (MFI) and relative strength index (RSI) yields abnormal returns on Helsinki, Oslo and Stockholm stock exchanges. The hybrid of MFI and RSI is a volume weighted RSI, which’ predictive power is solely based on utilization of historical stock prices and trading volumes. MFI-RSI hybrid measures market momentum and indicates ‘oversold’ and ‘overbought’ levels on the market oscillating between 0 and 100. The predictability of the market will be studied by applying the MFI-RSI vehicle on equally weighted country indices and a combined portfolio of the 450 stocks. The results indicate that MFI-RSI hybrid has trend predicting abilities at 5 % significance level on a bear market, but the transaction costs erode the profits on a bull market. The results suggest market efficiency in Finland, Norway and Sweden, yet the predictive power under distress market condition signals of a change in the investor sentiment during financial crisis. In addition to the excess returns, an insight is taken on the strategy’s risk reducing properties.
Keywords: Technical analysis; relative strength index; money flow index; predictive ability; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|